THE CHALLENGES OF BANK LENDING OF SMALL AND MEDIUM BUSINESSES: MODERN RUSSIAN SPECIFICITY - E. V. Travkina; T. S. Gushina (Вестник университета, 2020)
The role of lending to small and medium-sized businesses in the development of the modern Russian economy has been considered. Bank lending in this particular segment of the economy has been analyzed with highlighting the main trends and problems. The most important role of the Central Bank of the Russian Federation in solving the problems of lending to small and medium businesses through the monetary policy and the improvement of the regulatory framework has been determined. The main ways to solve the existing problems in the bank credit market of small and medium businesses have been identified. The state support for lending to small and medium business entities through partial subsidizing of interest rates has been considered thoroughly, models of partial government subsidizing of interest rates at the stage of obtaining a loan and at the stage of loan repayment have been presented.